2021
DOI: 10.3390/ijms22062815
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Computational Approach for the Discovery of Drug Delivery System Candidates for COVID-19

Abstract: In order to treat Coronavirus Disease 2019 (COVID-19), we predicted and implemented a drug delivery system (DDS) that can provide stable drug delivery through a computational approach including a clustering algorithm and the Schrödinger software. Six carrier candidates were derived by the proposed method that could find molecules meeting the predefined conditions using the molecular structure and its functional group positional information. Then, just one compound named glycyrrhizin was selected as a candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Again, it has further been proposed that licorice root membrane may be utilized to produce a bio-based antiviral face mask to limit COVID-19 spreading [144] . Again, based on the carrier stability scoring (CSS) method, glycyrrhizin was selected as the potential compound against SARS-CoV-2 [145] and was subjected to the formulation of micelle nanoparticles. In combination with nafamostat mesylate micelle, it was observed that these two compounds yielded synergistic activity against viral infection.…”
Section: Glycyrrhizin and Related Terpenoids As Effective Anti-sars-c...mentioning
confidence: 99%
“…Again, it has further been proposed that licorice root membrane may be utilized to produce a bio-based antiviral face mask to limit COVID-19 spreading [144] . Again, based on the carrier stability scoring (CSS) method, glycyrrhizin was selected as the potential compound against SARS-CoV-2 [145] and was subjected to the formulation of micelle nanoparticles. In combination with nafamostat mesylate micelle, it was observed that these two compounds yielded synergistic activity against viral infection.…”
Section: Glycyrrhizin and Related Terpenoids As Effective Anti-sars-c...mentioning
confidence: 99%
“…As stated before, GA plays key roles in different pathophysiological processes. In this context, the delivery of GA in a controlled and targeted manner may result in new and effective treatments for hepatocarcinoma, viral, and inflammatory diseases [65][66][67][68][69][70][71][72][73][74][75][76][77][78]. This section discusses recent reports that describe the development of new nanomedicine strategies for GA delivery, as summarized in Table 2.…”
Section: Antiviralmentioning
confidence: 99%
“…In vivo investigations using the MHV-A59-induced surrogate mouse model of COVID-19 showed that GA nanoparticles specifically target areas with severe inflammation, such as the lungs, which appeared to improve the accumulation of GANPs and enhance the effectiveness of the treatment [30]. In this sense, a recent interesting approach described a novel computational method named carrier suitability scoring (CSS) for identifying drug carrier candidates using molecular functional groups [78]. After computational analyses, GA and nafamostat mesilate (NM) were selected and converted into micelle nanoparticles to improve drug stability and to effectively treat COVID-19.…”
Section: Carbon Dots Glycyrrhizic Acid-based Carbon Dotsmentioning
confidence: 99%
“…Hence, to produce CD based tablets, molecular details, analyzing chemical group and molecular dynamics of CA-CD interaction need to be investigated by spectroscopy and molecular modeling [ 145 ]. Additionally, CAD approaches including a clustering algorithm and the Schrödinger software [ 146 ] machine learning (ML) techniques, ensemble learning, support vector machine, artificial neural networks and deep learning models [ 147 ] have been extended to recent pandemic concern, Covid 19 infection [ 148 ]. CAD and artificial intelligence provide new insight in colorectal cancer detection, screening and treatment especially in early stage of disease [ 149 ].…”
Section: Advanced Strategies For Crc Drug Deliverymentioning
confidence: 99%